Political Economy Analysis for Food and Nutrition Security - Reich, Michael R. (World Bank, Washington, DC, 2013)
The overall goal of this paper is to promote the use of political economy analysis in advancing more effective food and nutrition policies. The paper reviews the field of applied political economy for the food and nutrition sector, and offers practical guidance on how to conduct political economy analysis to better navigate the policy reform process. The paper is presented in three parts. Part I reviews the literature on political economy analysis (PEA) and its application in the food and nutrition fields, focusing on the applied literature in development. Three kinds of PEA are discussed: In-depth, Stakeholder, and Rapid Assessment PEA, which serve different purposes. The paper then introduces a structured qualitative method for conducting an in-depth PEA, based on four stages of the policy cycle: agenda-setting, policy design, policy adoption, and implementation. Part II provides an illustrative case study of an in-depth PEA for a specific food and nutritionrelated policy of India, the Integrated Child Development Services scheme. The analysis explains how the agenda was set and its consequences. Part III presents a newly developed tool to conduct a rapid assessment PEA for food and nutrition policy. This tool uses a questionnaire approach to evaluate the level of political commitment for food and nutrition security and opportunities for change, and can be used to monitor change in political commitment over time.